CompTIA security+ certification practice exams, (exam SY0-501) - Lachance, Daniel; Clarke, Glen E. (McGraw-Hill Education, 2017)
This fully updated, exam-focused study aid covers everything you need to know and shows you how to prepare for the CompTIA Security+ exam With hundreds of practice exam questions, including difficult performance-based questions, CompTIA Security+® Certification Study Guide, Third Edition covers what you need to know--and shows you how to prepare--for this challenging exam. •100% complete coverage of all official objectives for exam SY0-501 •Exam Watch notes call attention to information about, and potential pitfalls in, the exam •Inside the Exam sections in every chapter highlight key exam topics covered •Two-Minute Drills for quick review at the end of every chapter •Simulated exam questions--including performance-based questions--match the format, topics, and difficulty of the real exam Covers all exam topics, including: Networking Basics and Terminology • Security Terminology • Security Policies and Standards • Types of Attacks • System Security Threats • Mitigating Security Threats • Implementing System Security • Securing the Network Infrastructure • Wireless Networking and Security • Authentication • Access Control • Cryptography • Managing a Public Key Infrastructure • Physical Security • Risk Analysis • Disaster Recovery and Business Continuity • Computer Forensics • Security Assessments and Audits • Monitoring and Auditing Electronic Content Includes: • 50+ lab exercises and solutions •Complete practice exams •3+ hours of video training from the author •Secured book PDF.
Online resource; title from title page (Safari, viewed October 19, 2017)
Keywords: Computer security -- Study guides -- Examinations; Computer networks -- Study guides -- Security measures -- Examinations; Computer technicians -- Study guides -- Certification; Electronic data processing personnel -- Study guides -- Certification; Sécurité informatique; Examens; Guides de l'étudiant; Réseaux d'ordinateurs; Sécurité; Mesures; Examens; Guides de l'étudiant; Computer networks; Security measures; Examinations; Computer security; Examinations; Computer technicians; Certification; Electronic data processing personnel; Certification; examination study guides; Study guides; Guides de l'étudiant